Simulation and synthesis in medical imaging : first International Workshop, SASHIMI 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 21, 2016, Proceedings /: first International Workshop, SASHIMI 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 21, 2016, Proceedings. (2016) - Unknown
No abstract available